Implant-based Prosthetic Rehabilitation. Can We Go on a Legal Level? - Philippe PIRNAY (Romanian Society of Oral Rehabilitation, 2011)
The techniques of oral implants have been perfectly mastered for several years. However, we are currently witnessing a great excitement for implants, which, doubled by a commercial vulgarization, leads to a sometimes abusive or improperly controlled use of the procedure. The practitioner binds nevertheless to show extreme care and attention towards his patients, informing them on all scientific data, the practitioner's ethics and responsibility being at stake.